Co-generation of synthesis gas and C2+ hydrocarbons from methane and carbon dioxide in a hybrid catalytic-plasma reactor : a review - Istadi, Istadi; Amin, Nor Aishah Saidina (Elsevier BV, 2006)
The topics on conversion and utilization of methane and carbon dioxide are important issues in tackling the global warming effects from the two greenhouse gases. Several technologies including catalytic and plasma have been proposed to improve the process involving conversion and utilization of methane and carbon dioxide. In this paper, an overview of the basic principles, and the effects of CH4/CO2 feed ratio, total feed flow rate, discharge power, catalyst, applied voltage, wall temperature, and system pressure in dielectric-barrier discharge (DBD) plasma reactor are addressed. The discharge power, discharge gap, applied voltage and CH4/CO2 ratio in the feed showed the most significant effects on the reactor performance. Co-feeding carbon dioxide with the methane feed stream reduced coking and increased methane conversion. The H2/CO ratio in the products was significantly affected by CH4/CO2 ratio. The synergism of the catalyst placed in the discharge gap and the plasma affected the products distribution significantly. Methane and carbon dioxide conversions were influenced significantly by discharge power and applied voltage. The drawbacks of DBD plasma application in the CH4-CO2 conversion should be taken into consideration before a new plausible reactor system can be implemented.